Optical Coherence Tomography of the Retinal Ganglion Cell Complex in Leber's Hereditary Optic Neuropathy and Dominant Optic Atrophy. (3rd June 2019) - Asanad, Samuel; Tian, Jack J.; Frousiakis, Starleen; Jiang, Jerry P.; Kogachi, Kaitlin; Felix, Christian M.; Fatemeh, Darvizeh; Irvine, Anne Gority; Ter-Zakarian, Anna; Falavarjani, Khalil Ghasemi; Barboni, Piero; Karanjia, Rustum; et al.
ABSTRACT: Background : Mitochondrial optic neuropathies such as Leber's Hereditary Optic Neuropathy (LHON) and Dominant Optic Atrophy (DOA) have been shown to produce an optic neuropathy secondary to retinal ganglion cell loss with thinning of the retinal ganglion cell complex (RGCC). Methods : We performed a retrospective analysis assessing the thicknesses of the peripapillary retinal nerve fiber layer (pRNFL) along with the macular retinal ganglion cell-inner plexiform layer (RGC-IPL) using optical coherence tomography (OCT). We compared these changes among acute and chronic LHON, DOA, and normal healthy control patients. Results : Patients with chronic LHON exhibited statistically significant thinning of the RNFL in the superior, nasal, and inferior quadrants of the retina. In acute LHON, the RNFL was relatively thicker in all but the temporal quadrant when compared with respective quadrants in normal eyes; however, statistical significance was not achieved. In DOA, the RNFL was thinnest in the superior and inferior quadrants of the retina, measuring between acute and chronic LHON thickness values. In chronic LHON and DOA, both the pRNFL and RGC-IPL were significantly thinner in all four retinal quadrants relative to controls. Conclusions : This article represents the first comparative study of the RGCC between LHON and DOA. Our findings demonstrated significant thickness reductions in pRNFL and macular RGC-IPL in patients with LHON and DOA, with different specific patterns consistent with the general patterns of thinning classically observed. This study suggests the usefulness of the RGCC as a potential in vivo biomarker for assessing disease in patients with LHON and DOA.